Pemanfaatan Aplikasi Notion sebagai Pendukung Kemandirian Belajar Mahasiswa - Hanun, Naila; Qomario, Qomario; Utama, Agus Hadi; Dewi, Lazaro Kumala (Universitas Muhammadiyah Magelang, 2026)
This study analyzes the use of the Notion application by students to support self-regulated learning. Given the complexity of the productivity application's features, this study used a case study design with an embedded mixed-method approach. Participants consisted of five students selected purposively. Data were collected through a Likert-scale questionnaire adapted from the Motivated Strategies for Learning Questionnaire (MSLQ) and further deepened through interviews and dashboard observations. The results showed that Notion is associated with higher levels of student motivation and learning discipline. Features such as to-do lists and reminders proved effective for planning and time tracking. However, the findings revealed obstacles in the aspect of organizing material, where students struggled to optimize complex database features due to limited technical digital literacy. The conclusion of this study confirms that the Notion application has potential as a component of the Personal Learning Environment (PLE), but requires technical assistance at the beginning of the study period so that its function is not merely an ordinary digital notebook.